Aberrant Phex function in osteoblasts and osteocytes alone underlies murine X-linked hypophosphatemia - Baozhi Yuan; Masanori Takaiwa; Thomas L. Clemens; Jian Q. Feng; Rajiv Kumar; Peter S. Rowe; Yixia Xie; Marc K. Drezner (The Journal of Clinical Investigation, 2008)
Patients with X-linked hypophosphatemia (XLH) and the hyp-mouse, a model of XLH characterized by a deletion in the Phex gene, manifest hypophosphatemia, renal phosphate wasting, and rickets/osteomalacia. Cloning of the PHEX/Phex gene and mutations in affected patients and hyp-mice established that alterations in PHEX/Phex expression underlie XLH. Although PHEX/Phex expression occurs primarily in osteoblast lineage cells, transgenic Phex expression in hyp-mouse osteoblasts fails to rescue the phenotype, suggesting that Phex expression at other sites underlies XLH. To establish whether abnormal Phex in osteoblasts and/or osteocytes alone generates the HYP phenotype, we created mice with a global Phex knockout (Cre-PhexΔflox/y mice) and conditional osteocalcin-promoted (OC-promoted) Phex inactivation in osteoblasts and osteocytes (OC-Cre-PhexΔflox/y). Serum phosphorus levels in Cre-PhexΔflox/y, OC-Cre-PhexΔflox/y, and hyp-mice were lower than those in normal mice. Kidney cell membrane phosphate transport in Cre-PhexΔflox/y, OC-Cre-PhexΔflox/y, and hyp-mice was likewise reduced compared with that in normal mice. Abnormal renal phosphate transport in Cre-PhexΔflox/y and OC-Cre-PhexΔflox/y mice was associated with increased bone production and serum FGF-23 levels and decreased kidney membrane type IIa sodium phosphate cotransporter protein, as was the case in hyp-mice. In addition, Cre-PhexΔflox/y, OC-Cre-PhexΔflox/y, and hyp-mice manifested comparable osteomalacia. These data provide evidence that aberrant Phex function in osteoblasts and/or osteocytes alone is sufficient to underlie the hyp-mouse phenotype.